Pengaruh Kualitas Sistem, Kualitas Informasi, Kualitas Layanan Netflix Terhadap Kepuasan Pengguna di Instagram @Netflixid - Farah El Syafira; Widhihatmini Widhihatmini; Irawan Irawan (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2024)
This research is motivated by the development of information and communication technology, particularly media consumption in the entertainment industry. The Video on Demand (VOD) application Netflix is a pioneering service that is favored by the Indonesian community. In providing its services, Netflix must maintain high quality to compete and sustain its business. The aim of this research is to determine the influence of system quality, information quality, and Netflix service quality on users on Instagram @NetflixID. This study utilizes the Delone and Mclean (2016) Information System Success Model. A quantitative approach is employed, with purposive sampling for data collection. Data was gathered through questionnaires, and data analysis was conducted using PLS-SEM with SmartPLS 4.0 program. The results of this research indicate that there is a positive and significant effect of system quality on user satisfaction, with an effect size of 30.1%, a t-statistic of 2.674, and a p-value of 0.004. There is a positive and non-significant effect of information quality on user satisfaction, with an effect size of 23.5%, a t-statistic of 1.926, and a p-value of 0.055. There is a positive and significant effect of service quality on user satisfaction, with an effect size of 34.1%, a t-statistic of 3.214, and a p-value of 0.002. There is a combined effect of system quality, information quality, and service quality on user satisfaction at 61.4%.